Accuracy Of Colour Doppler Ultrasonography In Differentiating Benign From Malignant Thyroid Nodules - Mahesh kumar; Kelash Kumar; Ghazala Shahzad; Bhesham Kumar (ziauddin University, 2024)
Background: The prevalence of thyroid nodular disease is commonly found in iodine deficient areas. Majority of these nodules are benign and less than 5% of thyroid nodules being malignant. High resolution Ultrasonography is primary modality of choice in diagnosis of thyroid nodules. To determine the accuracy of Color Doppler ultrasonography in diagnosis of malignant thyroid nodule conformed on Fine needle aspiration cytology. Methods: This cross-sectional study was carried out in Department of Radiology PNS Shifa Hospital Karachi from 27th July 2012 to 26th February 2013. A total of 76 patients, having fixed palpable thyroid mass on examination, referred by clinicians for diagnostic workup were included in this study. Ultrasonography was performed using 7 MHZ linear array transducer. Thyroid nodule was assessed by grey scale sonographic features including number, size, echogenicity, margins and micro calcification. FNAC sampling was directed to the solid portion of the lesion. Cytological specimens were smeared according to the Papanicolaou technique, and were evaluated. All information was documented in the predesigned proformas. Results: Accuracy of Color Doppler Ultrasound in detection of malignant thyroid nodule was 92.1%, with sensitivity 75%, specificity 93%, positive predictive value 37.5%, and negative predictive value 98.5%. Conclusion: We found a comparable sensitivity and specificity to other international studies. An institutional protocol is devised to diagnose the malignant thyroid nodule as early as possible non-invasively employing Colour Doppler ultrasonography. This is helpful in early appropriate management of patients suffering from thyroid nodules. Key Words: Color Doppler ultrasonography, malignant thyroid nodule, Fine needle aspiration cytology